Current-induced magnetization switching in all-oxide heterostructures - Liu, Liang; Qin, Qing; Lin, Weinan; Li, Changjian; Xie, Qidong; He, Shikun; Shu, Xinyu; Zhou, Chenghang; Lim, Zhishiuh; Yu, Jihang; Lu, Wenlai; Li, Mengsha; et al. (Nature nanotechnology, 2019)
The electrical switching of magnetization through spin–orbit torque (SOT) 1 holds promise for application in information technologies, such as low-power, non-volatile magnetic memory. Materials with strong spin–orbit coupling, such as heavy metals 2 – 4 and topological insulators 5 , 6 , can convert a charge current into a spin current. The spin current can then execute a transfer torque on the magnetization of a neighbouring magnetic layer, usually a ferromagnetic metal like CoFeB, and reverse its magnetization. Here, we combine a ferromagnetic transition metal oxide 7 with an oxide with strong spin–orbit coupling 8 to demonstrate all-oxide SOT devices. We show current-induced magnetization switching in SrIrO 3 /SrRuO 3 bilayer structures. By controlling the magnetocrystalline anisotropy of SrRuO 3 on (001)- and (110)-oriented SrTiO 3 (STO) substrates, we designed two types of SOT switching schemes. For the bilayer on the STO(001) substrate, a magnetic-field-free switching was achieved, which remained undisturbed even when the external magnetic field reached 100 mT. The charge-to-spin conversion efficiency for the bilayer on the STO(110) substrate ranged from 0.58 to 0.86, depending on the directionality of the current flow with respect to the crystalline symmetry. All-oxide SOT structures may help to realize field-free switching through a magnetocrystalline anisotropy design. All-electrical switching of magnetization holds promise for applications in information technologies with low power consumption. Here, current-induced spin–orbit torque switches the magnetization in SrIrO 3 /SrRuO 3 bilayer structures at 70 K in the absence of an external magnetic field.